Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia